Dental anomalies in patients with down syndrome - Moraes, Mari Eli Leonelli de [UNESP]; Moraes, Luiz Cesar de [UNESP]; Dotto, Gustavo Nogara; Dotto, Patrícia Pasquali; Santos, Luis Roque de Araújo dos [UNESP] (FapUNIFESP (SciELO), 2007)
The purpose of the present study was to evaluate the incidence of dental anomalies in Brazilian patients with Down syndrome. A sample with 49 panoramic x-rays of syndromic patients aged 3 to 33 years (22 male and 27 female) was used. The characteristics of dental anomalies were observed in the panoramic radiographs in both the primary and permanent dentition, according to the ICD (International Classification of Diseases). The corresponding tables and percentile analysis were elaborated. There was a high incidence of syndromic patients with different types of anomalies, such as taurodontism (50%), proven anodontia (20.2%), suspected anodontia (10.7%), conic teeth (8.3%) and impacted teeth (5.9%). In conclusion, patients with Down syndrome presented a high incidence of dental anomalies and, in most cases, the same individual presented more than one dental anomaly.

O objetivo do presente estudo foi avaliar a incidência de anomalias dentárias em indivíduos brasileiros portadores de síndrome de Down. A amostra constou de 49 radiografias panorâmicas de indivíduos portadores com idade entre 3 e 33 anos, 22 do sexo masculino e 27 do sexo feminino. As características radiográficas das radiografias panorâmicas das anomalias dentárias foram observadas tanto nos dentes decíduos quanto permanentes de acordo com CID (Classificação Internacional de Doenças). Foi encontrada uma alta incidência dos mais variados tipos de anomalias, tais como taurodontismo (50%), anodontia comprovada (20,2%), suspeita de anodontia (10,7%), dentes cônicos (8,3%), dentes retidos (5,9%) e outras. Pela análise dos resultados podese observar que os indivíduos portadores de síndrome de Down apresentaram uma alta incidência de anomalias dentárias e, na maioria dos casos, um mesmo indivíduo apresentou mais de uma anomalia associada.
Keywords: Down syndrome; Trisomy 21; Tooth; Dental anomalies; Radiography; Panoramic radiograph